2020
DOI: 10.3390/ijerph17186732
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Study of Technology and Occupational Health in Healthcare Sector: A Worldwide Trend to the Future

Abstract: Since the eighties, technological tools have modified how people interact in their environment. At the same time, occupational safety and health measures have been widely applied. The European Agency for Safety and Health at Work considers that information and communication technologies are the main methods to achieve the goals proposed to improve working life and the dissemination of good practices. The principal objective was to determine the trends of publications focused on these technologies and occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Although there have been bibliometric analyses of articles in the field of food safety [ 11 , 12 ]; environmental health [ 13 , 14 ]; health promotion [ 15 , 16 ]; health education [ 17 ]; mental health [ 18 , 19 ]; sport health [ 20 ]; and occupational health [ 21 , 22 ], the entire category of Public, Environmental & Occupational Health has never been studied worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been bibliometric analyses of articles in the field of food safety [ 11 , 12 ]; environmental health [ 13 , 14 ]; health promotion [ 15 , 16 ]; health education [ 17 ]; mental health [ 18 , 19 ]; sport health [ 20 ]; and occupational health [ 21 , 22 ], the entire category of Public, Environmental & Occupational Health has never been studied worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the literature review, it can be argued that there are benefits for mainstreaming OSH in education in the fight against work-related accidents. Ultimately, efforts towards mainstreaming OSH in education may play a significant role in shaping the safety attitudes of the students, and leveraging them in times of tough challenges of the labour market [99,135]. However, the EU-OSHA, which supports that mainstreaming OSH in education should be a priority throughout the universities' curriculum, reports that such integration is the most challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a recent study, the highest production was described in the United States, followed by the United Kingdom, Australia, and Canada [ 2 ], while another study revealed that it was the United States, United Kingdom, China, Canada, and Australia [ 4 ]. In a study on the occupational health of health workers, the most prolific countries were the same as those mentioned above [ 6 ], while in a similar study, Brazil, and South Africa predominated [ 15 ].…”
Section: Discussionmentioning
confidence: 99%